Advanced diagnostic and therapeutic strategies in nanotechnology for lung cancer - Duan, Yujuan; Shen, Chen; Zhang, Yinan; Luo, Yao (Frontiers in Oncology, 2022)
As a highly invasive thoracic malignancy with increasing prevalence, lung cancer is also the most lethal cancer worldwide due to the failure of effective early detection and the limitations of conventional therapeutic strategies for advanced-stage patients. Over the past few decades, nanotechnology has emerged as an important technique to obtain desired features by modifying and manipulating different objects on a molecular level and gained a lot of attention in many fields of medical applications. In lung cancer, nanotechnology has proven to be more effective and specific in detecting extracellular cancer biomarkers and cancer cells in vitro, as well as imaging cancer in vivo, compared to traditional methods; Nanoscale drug delivery systems have developed rapidly to overcome various forms of multi-drug resistance and reduce detrimental side effects to normal tissues by targeting cancerous tissue precisely. There is no doubt that nanotechnology has the potential to enhance healthcare systems by simplifying and improving cancer diagnostics and treatment. Throughout this review, we summarize and highlight recent developments in nanotechnology applications for lung cancer in diagnosis and therapy. Moreover, the prospects and challenges in the translation of nanotechnology-based diagnostic and therapeutic methods into clinical applications are also discussed.